Metacognition Of the Twelfth-Grade Students in Extensive Reading - Kristinus Sembiring; Marianus Paulino Mada; Ubaldus Djonda; Lio Stefanus; Elvis Albertus Bin Toni (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2025)
Many studies examine metacognitive strategies in reading. But this study examines the metacognitive strategies employed by Year 12 students at SMAK Syuradikara Ende during extensive reading activities, with the aim of identifying the use of planning, monitoring, and evaluation strategies. This study employed a mixed-methods approach. It combined quantitative data from questionnaires with qualitative data from semi-structured interviews. The research participants were 80 students. They were chosen purposively, namely, those who participated in extensive reading activities during classroom learning. Descriptive statistics were used to analyze the quantitative data, whilst the qualitative data were used to explore the students’ reading practices and experiences. The results of the study indicate that students applied metacognitive strategies in varying ways and with varying frequencies. Students frequently used the strategies of visualization, goal-setting, inferring meaning from context, and summarizing. The strategy of visualization was dominant. Contrariwise, two strategies were still used inconsistently: activating prior knowledge and identifying comprehension problems through self-questioning. These findings encourage educators to use metacognitive strategies in extensive reading to improve pupils’ performance and encourage them to overcome difficulties before, during, and after writing. Furthermore, research could investigate the factors influencing the use of these strategies.